Psychosocial factors Responsible for the Institutionalization of Juveniles and their Institutional life - Niloufer.M (International Journal of Research in Social Sciences, 2015)
India facts 440 million children live in India (aged below 18 years) constitute 42% of India‟s total population; one-third of them live in conditions of abject poverty and neglect. Kerala ranks third in the issue of violence against children, 1 in 5 children are sexually abused in Kerala, and 56.10% of children in Kerala were physically abused in one or more situation. According to Juvenile Justice Act, there are two major classifications of Juveniles, Children in Conflict with law and Children in need of Care and Protection. This study mainly focuses on Children in need of Care and Protection of Thrissurs Juvenile Home. Researcher selected “Descriptive Research Design” and 60 Juveniles as sample size for the study. Using Structured Questionnaire, collected secondary data through interviewed the respondents. The major findings of the study are, 44% of Juveniles under the Institutionalized are coming under the age group of 11-14 years, Child Abuse is the major reason for Institutionalization (34%), Alcoholism of Parents and Consequent problems are more prone in these Children‟s Families, 56% of juveniles are satisfied with the services provided by the Juvenile Home including educational and recreational services.Through this study, Alcoholism, Family Conflict, Economic constraints, Peer group influence etc are the major factors for Institutionalization and Community Health centers, Counseling Centers and Social workers have had major role in these areas.